Improving high temperature tribological performances of Si doped diamond-like carbon by using W interlayer. (June 2020) - Yu, Weijie; Wang, Junjun; Huang, Weijiu; Cui, Longchen; Wang, Linqing
Abstract: Diamond-like carbon films (DLC) with different silicon contents combined with W interlayer are deposited by plasma-assisted reactive magnetron sputtering. The structures and high-temperature tribological properties of the films are investigated. The results reveal that the pure DLC film is worn out at 400 °C because of graphitization, while the Si-DLC film with Si content of 4.56 at.% keeps low friction coefficient (0.2–0.05) at high temperature up to 500 °C. The 14.56 at.% Si-DLC film failed at 500 °C induced by the formation of SiO2 . The improved high-temperature tribological performance of the 4.56 at.% Si-DLC film is attributed to the tribochemistry of W interlayer at 500 °C which formed a film composed of tungsten oxides and carbide. Highlights: DLC films (pure DLC, 4.56 at.% and 14.56 at.% Si-DLC) with W interlayers are deposited by reactive magnetron sputtering.. The structure and in situ high-temperature tribological properties of the films are investigated. 4.56 at.% Si-DLC film with W interlayer forms a new layer at 500 ℃ to lower the COF and its formation mechanism is discussed.